Iso 14001 Implementation Impact And Financial Performance On Corporate Social Responsibility Disclosure - Daniel T H Manurung, Radhi Abdul Halim Rachmat (Jurnal Manajemen, 2019)
This study aims to determine the impact of implementing ISO 14001, Financial Performance is proxied by ROA and ROE on Corporate Social Responsibility Disclosures in non-financial companies that are listed on the Indonesia Stock Exchange in 2014-2016. The study used secondary data from the annual financial report and sustainability report on the Basic Industry and Chemical Industry sub-sector manufacturing industry listed on the Indonesia Stock Exchange in 2014 - 2016. The sample technique used purposive sampling method, while for the study 20 samples of manufacturing companies and research methods used analysis multiple regression. The results showed that the impact of implementing ISO 14001 had a positive effect on disclosure of corporate social responsibility, financial performance variables through return on assets had a negative and significant effect on disclosure of corporate social responsibility and financial performance through return on equity had a positive effect on disclosure of corporate social responsibility.